Determination of Routin Compound Content of Moringa Folium (Moringa oleifera) using Several Extraction Methods - Hasnaeni, Hasnaeni; Rosandy, Andi Rifki; Apridamayanti, Pratiwi; Permadi, Adi; Rumaisha, Sanda (Jurnal Fitofarmaka Indonesia, 2023)
Extraction has been carried out from Moringa folium using the Microwave-Assisted Extraction (MAE), Ultrasound-Assisted Extraction (UAE) and Reflux Extraction (RE) methods. Moringa Folium has many uses, including as a chemopreventive agent. In this research, identification was carried out to determine the compounds in Moringa folium. Extraction uses the MAE, UAE, and Reflux methods. The of chemical compound content was determined using HPLC and standardized of rutin. The identification results showed that the Moringa folium spectra were similar to the routine spectra.